Characteristics of Structural and Functional State of Musculoskeletal System in Patients with Juvenile Rheumatoid Arthritis - N.N. Kaladze; Ye.V. Sarchuk (Zaslavsky O.Yu., 2012)
In the article there are presented the findings of investigation of the characteristics of structural and functional state of musculoskeletal system in patients with juvenile rheumatoid arthritis depending on form of disease.